2004
DOI: 10.1086/427076
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Fisk-Type Heliospheric Magnetic Field on Cosmic-Ray Modulation

Abstract: The Fisk model of the heliospheric magnetic field (HMF) has proved to be quite difficult to implement in three-dimensional numerical modulation codes. We have developed a divergence-free Fisk-Parker hybrid HMF that is easier to implement and that should be a reasonable approximation for the case when field lines open into the heliosphere both in the polar coronal holes and at low latitudes. To study the effects of this hybrid field on galactic cosmic rays, we solve the three-dimensional steady state Parker tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…The latter is called the modified Fisk field B mF . The Fisk field is used in the hybrid representation by Burger & Hitge (2004), where a Parker-like field dominates in the ecliptic and over the poles, while in between a Fisk-like field contributes most to the HMF.…”
Section: Analytic Hmf Representationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is called the modified Fisk field B mF . The Fisk field is used in the hybrid representation by Burger & Hitge (2004), where a Parker-like field dominates in the ecliptic and over the poles, while in between a Fisk-like field contributes most to the HMF.…”
Section: Analytic Hmf Representationsmentioning
confidence: 99%
“…The assumption of a constant solar wind speed in this field, was abandoned by , see also Schwadron et al (2008). For a deeper discussion of these HMFs, see Burger & Hitge (2004), Burger (2005), and Burger et al (2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The end result is a field line that moves in heliographic latitude. Over the last ten years, various attempts to incorporate the Fisk field into numerical modulation models have been reported (Kóta & Jokipii 1999;Burger et al 2001;Burger & Hitge 2004). A recent overview of various models for the heliospheric magnetic field, including Fisk-type fields, is given by Burger (2005).…”
Section: The Heliospheric Magnetic Fieldmentioning
confidence: 99%
“…[4] Several authors have suggested modifications of both fields [Jokipii and Kota, 1989;Smith and Bieber, 1991;Schwadron, 2002;Burger and Hitge, 2004;Burger et al, 2008;Schwadron et al, 2008], which have been quantitatively compared in a study by Scherer et al [2010]. Although very useful for many purposes, these analytical representations of the HMF cannot be used to reproduce actual measurements in sufficient detail at any given time in the solar activity cycle.…”
Section: Introductionmentioning
confidence: 99%